Tahlīl al-Jumlah al-Mu’robah fī al-Qur’āni Sūroti Maryam wa Tathbīquhā fī Ta’līmi ‘Ilmi an-Nahwi - Megawati, Megawati; Nurhayati, Dewi (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
This research aims to describe the Jumlah Mu’robah contained in the Qur'an surah Maryam, to classify the Jumlah Mu’robah in the al-Qur'an surah Maryam, and to find out the implications of the Jumlah Mu’robah on nahwu learning material. This research used a qualitative research design by implementing a library type of research. The date were collected through documentation techniques. The data in this study is the Jumlah Mu’robah contained in Surah Maryam. The result of this study showed that there 178 Jumlah Mu’robah found in the surah maryam, consisting of 10 Jumlah ismiyah, 116 Jumlah fi'liyah, and 48 Jumlah nasikhah (21 from kaana wa akhwatuha; and 27 from inna wa akhwatuha 21), and 4 were Jumlah haliyah. The result of this study can used as reference for other research having similar research context.